2019
DOI: 10.3390/ijms20051189
|View full text |Cite
|
Sign up to set email alerts
|

AdRAP2.3, a Novel Ethylene Response Factor VII from Actinidia deliciosa, Enhances Waterlogging Resistance in Transgenic Tobacco through Improving Expression Levels of PDC and ADH Genes

Abstract: APETALA2/ethylene-responsive factor superfamily (AP2/ERF) is a transcription factor involved in abiotic stresses, for instance, cold, drought, and low oxygen. In this study, a novel ethylene-responsive transcription factor named AdRAP2.3 was isolated from Actinidia deliciosa ‘Jinkui’. AdRAP2.3 transcription levels in other reproductive organs except for the pistil were higher than those in the vegetative organs (root, stem, and leaf) in kiwi fruit. Plant hormones (Salicylic acid (SA), Methyl-jasmonate acid (Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The genes influence the alcoholic fermentation process such as ADH1-1 , ADH1-2 , ADH1-3 , PDC1 , and PDC2 induced and suppressed in overexpressed and silenced plants, respectively ( Yin et al, 2019 ). Similarly, the induced expression levels of NtPDC , NtADH , NtHB1 , NtHB2 , NtPCO1 , and NtPCO2 genes in AdRAP2.3 overexpressed tobacco plants presented its association with the enhanced waterlogging stress tolerance ( Pan et al, 2019 ). In wheat, waterlogging stress can significantly hinder the physiological activities particularly photosynthesis, which ultimately reduce the grain yield and affect overall yield.…”
Section: Inducing Waterlogging Tolerance Via Genetmentioning
confidence: 99%
“…The genes influence the alcoholic fermentation process such as ADH1-1 , ADH1-2 , ADH1-3 , PDC1 , and PDC2 induced and suppressed in overexpressed and silenced plants, respectively ( Yin et al, 2019 ). Similarly, the induced expression levels of NtPDC , NtADH , NtHB1 , NtHB2 , NtPCO1 , and NtPCO2 genes in AdRAP2.3 overexpressed tobacco plants presented its association with the enhanced waterlogging stress tolerance ( Pan et al, 2019 ). In wheat, waterlogging stress can significantly hinder the physiological activities particularly photosynthesis, which ultimately reduce the grain yield and affect overall yield.…”
Section: Inducing Waterlogging Tolerance Via Genetmentioning
confidence: 99%
“…As one of the biggest transcription factor families in plants, WRKYs reportedly regulate gene expression mainly via W box CEs (Yang et al, 2018;Abeysinghe et al, 2019;Liu et al, 2019). Previous studies have revealed that ERF-VII genes play a positive key role in response to low-oxygen stress conditions in Arabidopsis thaliana (Gibbs et al, 2015;Papdi et al, 2015;Pan et al, 2019;Wei et al, 2019), which has five members: RAP2.2, RAP2.3, RAP2.12, HRE1 and HRE2. We then found that promoters of four of them contain the W-box CEs (http://bioinf ormatics.psb.ugent.be/webtools/plantcare/html/) (Figs 4c, S3a).…”
Section: Wrky12 Also Positively Modulates Submergence Responsementioning
confidence: 99%
“…Specifically, AP2/ERF is one of the largest plant transcription factor families participating in plant development and resistance to biotic and abiotic stresses. It has been characterized based on either one or two AP2 domains, where the ERF subfamily has one AP2 domain ( Pan et al ., 2019 )⁠. Plant hormones as salicylic acid (SA), methyl-jasmonate acid (MeJA), 1-aminocyclopropanecarboxylic acid (ACC), and abscisic acid (ABA), besides abiotic (including NaCl) and biotic stresses, could induce the expression of RAP2-3 gene ( Pan et al ., 2019 )⁠.…”
Section: Discussionmentioning
confidence: 99%